ANALISIS KESALAHAN BUKU MATEMATIKA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL SERTA ALTERNATIF PENYELESAIANNYA - Abdur Rohim (JEDMA Jurnal Edukasi Matematika, 2022)
Textbooks are one of the important media in learning. The quality of textbooks affects students' understanding. One way to determine the quality of a textbook is to analyze the book. This study aims to analyze the errors of the Mathematics book on the Two Variable Linear Equation System (SPLDV) material contained in the Class VIII Junior High School Student Book. The method used in this research is a qualitative method with a descriptive approach. The results showed that there were still some errors. Eight conceptual errors, three drawing errors and seven writing errors. The results of the study can be used as material for consideration in improving the book. So as not to be bad for students who use the book